The geometry and petrogenesis of dolomite hydrocarbon reservoirs - Braithwaite, C. J. R.; Rizzi, G.; Darke, G. (Geological Society special publication ;, 2004)
The wide distribution of dolomite rocks in North American, Middle- and Far-Eastern hydrocarbon reservoirs is reason enough for their intensive study. In this volume dolomite enthusiasts review progress and define the current boundaries of dolomite research, related particularly to the importance of these rocks as reservoirs.